Urban-Rural Differences in Level of Various Forms of Trust in Hungary - Tamas Dusek; Eva Palmai (European Regional Science Association (ERSA), 2015)
This study examines the association between urban/rural residence and various forms of trust in Hungary, including control variables such as age, gender, income, marriage, qualification into the analysis. Trust is a basic dimension of human capital and a very often used concept in everyday situations too. Trust research became increasingly popular in recent years. However, urban-rural and spatial differences of specific forms of trust remains a rarely investigated question. Trust can be measured with one question (global or general trust) or with many questions. Global measures of trust have serious methodological and interpretative problems. Therefore a research was conducted with 19 questions concerning the various personal or impersonal subjects of trust. Respondents (n=2031) of a countrywide representative survey in Hungary rated their trust in various groups or institutions on a 10-point Likert scale. The results were analysed along the settlement hierarchy at four different levels: Budapest, the country capital; cities with county rights (namely the biggest Hungarian cities, apart from Budapest); smaller and medium sized cities; villages. Various sociodemographic factors were included into the analysis. In some cases age and gender is a more significant factor in differentiating the results as the settlement type, but age and gender can have a different effect on results for different settlement types. The results have a great variability according to the subject of trust. General differences between settlement types show a higher trust level in cities with county rights, then towns, villages and at last Budapest. Exceptions from this general picture are highly interesting: trust in personal contacts is much lower in Budapest, trust in institutions or abstract institutions (law and legal system, market system, political system, banks) is higher than in villages, institutions with more concrete personal contacts is higher in villages than in Budapest. The difference is bigger in the case of church. In Budapest, compared to other settlements, trust is lower in personal contacts, but the differences between settlement categories are lower than the differences of trust between the personal and impersonal contacts. Gender differences according to the settlement categories are also interesting. The highest trust level can be seen in elder age. However, trust of younger adults is higher in Budapest, mainly thanks to the much higher trust level in abstract institutions. Trust of younger adults in personal contacts and health institutions is not higher in Budapest. These are just some of the main finding of our complex results.
Keywords: R5; R20; 330; urban-rural differences; trust; territorial capital